Pemanfaatan Aplikasi Wordwall Untuk Meningkatkan Pemahaman Materi Sejarah Pergerakan Nasional Indonesia - Kailuhu, Jacomina Selfisina; Kempa, Titin (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
As technology develops, digital-based learning media is increasingly being used in higher education. The Wordwall application is a platform that allows lecturers and students to interact more dynamically through various educational game formats. This research aims to determine the effectiveness of using the Wordwall application in increasing students' understanding of the material on the History of the Indonesian National Movement. After application, it will be seen whether it is useful or not. In this research, researchers used a qualitative approach with a descriptive approach. The reason for using this research method is because the researcher wants to know and provide a detailed, clear and concrete description of the use of the Wordwall application to increase understanding of the historical material of the Indonesian national movement. The Wordwall application enables interactive learning through quizzes, puzzles and educational games which make the learning process more interesting and dynamic. This study was conducted on students in the 4th semester of the Pattimura University history education study program in the history of the Indonesian National Movement course, and the results showed that Wordwall was able to increase students' participation, understanding and memory of the material being taught.